Cooperative language learning to develop english oral production in tenth-year students at Luis Ulpiano de la Torre high school in Cotacachi, the school year 2021- 2022 - Naranjo Proaño, Mercedes Liliana (2025)
To propose Cooperative Language Learning Strategies for English Foreign Language Teachers to improve students' speaking comprehension in tenth-grade students at “Luis Ulpiano de la Torre” High School.